Govor in govorna komunikacija v učnih načrtih za osnovno šolo in gimnazijo ter v katalogih znanj: Simona Pulko, Melita Zemljak Jontes (Stanje in perspektive uporabe govornih virov v raziskavah govora, 2024)
Speech and Speech Communication in Curricula for Elementary School, Secondary Schools and in Catalogues of Knowledge. Speech is a human activity that is important primarily of its communicative language function. A child's development requires appropriate support and role models from birth in order to create opportunities for learning to communicate. Speech plays an individual role in one's development and a social role in communication with the environment. One of the fundamental goals of language learning at school is the development of communication skills in the Slovene (literary) language, i.e. the practical and creative mastery of all communication activities (including speaking) and the basics of the language system. The analysis provides an overview of teaching the speech, teaching strategies and the emphasis on the development of speaking skills in the curricula for Slovene in primary schools (2011, 2018), the curricula for Slovene in secondary schools (2008) and the catalogues of knowledge for Slovene. One of the research goals was also to focus on the standard pronunciation development and the development of orthographic skills, including different types of transcription, depending on the level of education.